Quantitative assessment of UML dynamic models. - Baroni, Aline Lúcia
In this work we plan to provide a suite of measures to address mainly two problem areas within contemporary object-oriented software measurement: (i) the lack of measures for the early stages of system development, like conceptual modeling and (ii) the lack of measures for dynamic models of an object-oriented system. Our suite of measures is going to be taken from UML 2.0 diagrams. OCL (Object-Constraint Language) and the UML 2.0 meta-model will be used to formalize and contextualize the definitions.
Keywords: Software; Software engineering; Design tools and techniques; Object oriented design methods; State diagrams; Metrics; Product metrics; Programming languages; Language classifications; Design languages; Constraint and logic languages; Object oriented languages; Design; Experimentation; Measurement; OCL; UML; Meta-model.; UML models (use cases, statecharts, activity, sequence, collaboration, communication).; Behavioral models; Dynamic models; Estimation; Formalization; Object-oriented design metrics